2008
DOI: 10.2147/cia.s204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a group-based exercise program on balance in elderly

Abstract: Objective:To determine the effectiveness of 8-week group functional balance training classes on balance outcomes in community-dwelling veterans at risk for falls.Design:Pre-test, post-test using retrospective data.Setting:VISN 8 Patient Safety Center at James A. Haley Veterans Hospital in Tampa, FL, USA.Participants:Fifty one community living veterans with mean age of 78 at risk for falls.Intervention:Participants received a weekly 1-hour functional balance training class for 8 weeks in a small group setting (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 14 publications
4
35
1
3
Order By: Relevance
“…BBS, TUG and Berg balance scale indices were all significantly improved after the treatment in patients receiving balance training with BBS. Bulat and colleagues observed that a balance training class was safe and effective in improving balance outcomes in a cohort of elderly veterans at risk for falls with significant increase in berg balance score [Bulat et al 2007]. The usefulness of balance training with BBS in improving postural stability and balance is welldemonstrated in previous studies in elderly people, especially those with neuropathy, diabetes and DN [Akbari et al 2006[Akbari et al , 2012Salsabili et al 2011].…”
Section: Discussionmentioning
confidence: 94%
“…BBS, TUG and Berg balance scale indices were all significantly improved after the treatment in patients receiving balance training with BBS. Bulat and colleagues observed that a balance training class was safe and effective in improving balance outcomes in a cohort of elderly veterans at risk for falls with significant increase in berg balance score [Bulat et al 2007]. The usefulness of balance training with BBS in improving postural stability and balance is welldemonstrated in previous studies in elderly people, especially those with neuropathy, diabetes and DN [Akbari et al 2006[Akbari et al , 2012Salsabili et al 2011].…”
Section: Discussionmentioning
confidence: 94%
“…As a result it has been suggested that circuit class training may be a more efficient means of providing physiotherapy interventions when compared to more traditional one to one models. 16 Future research is required to further investigate the cost benefit of such a model for people with PD. Patient satisfaction with the program was remained high, which suggesting that there may be other potential benefits to participation.…”
Section: Discussionmentioning
confidence: 99%
“…15 Participants may complete a series of workstations arranged in a circuit 15 or may complete a series of individualised exercises within a group setting. 16 Circuit class therapy differs from the conventional one therapist to one patient model as there are usually more than two patients involved at any one time. 16 Circuit class therapy has been shown to be effective in improving the mobility of people early after stroke, 16 in chronic stroke patients 17 and in people with a history of falls 18 Circuit class therapy has the potential to be a more effective means of providing a greater amount of physical therapy for people both within the hospital setting and in the community outpatient setting.…”
mentioning
confidence: 99%
See 2 more Smart Citations